Asterocherids (Copepoda: Siphonostomatoida) associated with marine invertebrates in the Strait of Gibraltar - Conradi, Mercedes; Bandera, Mª Eugenia (Zootaxa, 2011)
Six years ago, an ongoing sampling programme to seek symbiont copepods was initiated in the Strait of Gibraltar. Most of the copepod species reported in this area (48%) belonged to the families Notodelphyidae and Botryllophilidae and nearly 30% of them were new to science. This paper describes a new species of Asterocheres (Asterocheridae, Siphonostomatoida) and redescribes two poorly known species of this genus. Asterocheres tarifensis n. sp. was found living in association with Astroides calycularis, a coral that hosts a variety of symbiotic copepods. This new species differs from its congeners by the possession of the following combined characters: body cyclopiform, 21-segmented antennule in female, 2-segmented mandibular palp, siphon reaching the insertion of maxilliped, maxilla without aesthetasc, maxilliped 5-segmented, armature of the antennary exopod consisting of two setae, inner lobe and outer lobe of maxillule each armed with four setae, genital area armed with two setae, fifth leg exopod with three setae, and caudal rami about as long as wide. Furthermore, two poorly known Asterocheres species are redescribed revealing some discrepancies with their previous descriptions. Asterocheres minutus is characterized by having a 21-segmented antennule, a very short oral siphon, a 1-segmented mandibular palp, and the two lobes of the maxillule with a similar length. The cladistic model of budding hypothesis is proposed for the origin of the two sibling Asterocheres species: A. minutus and A. echinicola. Asterocheres siphonatus is distinguished by a combination of characters that include a 21-segmented antennule, an oral siphon extending to the intercoxal plate of leg 4 and the 1-segmented mandibular palp. The controversy concerning the name of this species is also studied.